Numerical computation of solitary wave solutions of the Rosenau equation - Erbay, H.A.; Erbay, S.; Erkip, A. (Wave motion, 2020)
We construct numerically solitary wave solutions of the Rosenau equation using the Petviashvili iteration method. We first summarize the theoretical results available in the literature for the existence of solitary wave solutions. We then apply two numerical algorithms based on the Petviashvili method for solving the Rosenau equation with single or double power law nonlinearity. Numerical calculations rely on a uniform discretization of a finite computational domain. Through some numerical experiments we observe that the algorithm converges rapidly and it is robust to very general forms of the initial guess. •A Petviashvili iteration method was used to solve the Rosenau equation numerically.•Solitary wave solutions were obtained for single and double power law nonlinearities.•Existence of the high-order dispersive term leads to the existence of non-monotonic tails.•The iteration scheme converges rapidly and it is robust to forms of initial guess.